The growth advantage a business blueprint for the ultimate competitive edge - Lisser, Robert, 1959- (Rowman & Littlefield, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2022)
"The Growth Advantage cracks open the business secrets that teach companies how to achieve that dream of steady, predictable growth through effective planning and solid execution. Readers learn how their company can develop and sustain a blueprint for growth that guides company actions on a daily and weekly basis. Combining elements of culture, strategy, planning, execution, talent acquisition, training, motivation, accountability, and brand differentiation into one book with clear, actionable steps, Bob Lisser brings readers along a journey that starts with a plan and ends with success"--